Number of meal components, nutritional guidelines, vegetarian meals, avoiding ruminant meat: what is the best trade-off for improving school meal sustainability? - Poinsot, Romane; Vieux, Florent; Maillot, Matthieu; Darmon, Nicole (European Journal of Nutrition, 2022)
Purpose: School meals have the potential to promote more sustainable diets. Our aim was to identify the best trade-off between nutrition and the environment by applying four levers to school meals: (i) reducing the number of meal components, (ii) complying with the French school nutritional guidelines, (iii) increasing the number of vegetarian meals, and/or (iv) avoiding ruminant meat. Methods: Levers were analyzed alone or in combination in 17 scenarios. For each scenario, 100 series of 20 meals were generated from a database of 2316 school dishes using mathematical optimization. The nutritional quality of the series was assessed through the mean adequacy ratio (MAR/2000 kcal). Seven environmental impacts were considered such as greenhouse gas emissions (GHGE). One scenario, close to series usually served in French schools (containing four vegetarian meals, at least four ruminant meat-based meals, and at least four fish-based meals) was considered as the reference scenario. Results: Reducing the number of meal components induced an important decrease of the energy content but the environmental impact was little altered. Complying with school-specific nutritional guidelines ensured nutritional quality but slightly increased GHGE. Increasing the number of vegetarian meals decreased GHGE (from 11.7 to 61.2%) but decreased nutritional quality, especially when all meals were vegetarian (MAR = 88.1% against 95.3% in the reference scenario). Compared to the reference scenario, series with 12 vegetarian meals, 4 meals containing fish and 4 meals containing pork or poultry reduced GHGE by 50% while maintaining good nutritional quality (MAR = 94.0%). Conclusion: Updating French school nutritional guidelines by increasing the number of vegetarian meals up to 12 over 20 and serving non-ruminant meats and fish with the other meals would be the best trade-off for decreasing the environmental impacts of meals without altering their nutritional quality.